Viability Test of Photodynamic Therapy with Diode Laser Waves Length 405 nm on BHK-21 Fibroblast Cells with Various Irradiation Distances - Sri Kunarti; Vina Zavira Nizar; Widya Saraswati (Conservative Dentistry Journal, 2019)
Background: Photodynamic therapy has now become popular, but its cytotoxic effect is still unclear. In order to be considered suitable for oral cavity therapy, the therapy must not be toxic or cause adverse effects on the target tissue. Viability testing for photodynamic therapy is important to do. Fibroblast cells are often used for testing the toxicity of dentistry because they are the most important cells in the components of the pulp, periodontal ligament, and gingiva. Purpose: To prove the effect of irradiation distance on photodynamic therapy on the viability of BHK-21 fibroblast cells. Method: Viability test was performed with BHK-21 fibroblast cells placed on a 96 well microplate which was then irradiated with 405 nm photodynamic therapy with varying irradiation distances of 1, 4, 7, 10, 13, and 16 mm. After irradiation, cell viability was tested by MTT assay and ELISA Reader. Data were analyzed using Kolmogorov-Smirnov, Levene’s test, Kruskall Wallis, and Tukey HSD. Result: Fibroblast cells with 4 mm irradiation distance have viability over control cells, whereas at irradiation distances 1, 7, 10, 13, and 16 mm have less viability than control cells. Conclusion: Photodynamic therapy 405 nm with 4 mm irradiation distance gives a biostimulation response so that the viability of BHK-21 fibroblast cells increases.